Three essays on corporate finance studies in China : a thesis presented in fulfilment of the requirements for the degree of Doctor of Philosophy in Finance at Massey University, Palmerston North, New Zealand - Yue, Shuai (Massey University, 2023)
This thesis investigates three aspects of listed firms in the Chinese market. The first essay in the thesis examines the impact of state ownership on firm performance using hand collected ownership data of firms with state-private mixed ownership structures. We find a U-shaped relationship between state ownership and firm performance. At lower levels, state ownership has a negative association with firm performance, but beyond a certain threshold (e.g., 55% for ROA and 44% for Tobin's Q), state ownership becomes positively associated with firm performance. This finding indicates a trade-off between the negative effects of grabbing hand and the monitoring benefits of state owners. In addition, the introduction of strategic investors moderates the influence of state ownership on firm performance. The results show that the U-shaped impact of state ownership on firm performance diminishes after the introduction of strategic investors, implying that strategic investors may mitigate the underperformance observed around the threshold state ownership levels. The second essay focuses on the corporate information environment. It investigates the behaviour of firms with politically connected executives regarding information disclosure when subject to government inspection influences. China initiated the central environmental protection inspection in 2016. We find that while firms with politically connected executives generally exhibit lower stock price crash risk, these politically connected firms are more prone to crash risk when subject to inspection influences than firms without political connections. Further, we examine whether the inspection effect on crash risk varies based on the type of political connections developed by executives, namely achieved and ascribed political connections. Our results show that firms with executives having achieved political connections are related to higher crash risk when under government inspection influences, but no significant impact is observed for firms with executives having ascribed political connections. The final essay examines the influence of firms’ exposure to economic policy uncertainty (EPU) on environmental investment and investigates whether firm size plays a significant role in this relationship. We find that although small firms are generally associated with lower levels of environmental investment compared to large firms, there is a positive association between small firms’ EPU exposure and environmental investment, indicating that small firms are more inclined to invest in environmental initiatives when facing higher EPU exposure.
Keywords: Business and politics; Corporate governance; Corporations; Political activity; Investments; Environmental aspects; China; ownership structure; political connections; economic policy uncertainty; 350204 Financial institutions (incl. banking)